2008
DOI: 10.1186/1475-2840-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of streptozotocin-induced diabetes on myocardial blood flow reserve assessed by myocardial contrast echocardiography in rats.

Abstract: The role of structural and functional abnormalities of small vessels in diabetes cardiomyopathy remains unclear. Myocardial contrast echocardiography allows the quantification of myocardial blood flow at rest and during dipyridamole infusion. The aim of the study was to determine the myocardial blood flow reserve in normal rats compared with Streptozotocin-induced diabetic rats using contrast echocardiography. Methods:We prospectively studied 40 Wistar rats. Diabetes was induced by intravenous streptozotocin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
2
24
1
1
Order By: Relevance
“…Using this technique it has been shown that myocardial blood flow reserve, as a measure for vascular function, is reduced in type 1 diabetic rats [8] and type 1 diabetic patients [9] when compared to normoglycaemic controls. There are currently limited data available on myocardial perfusion in glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique it has been shown that myocardial blood flow reserve, as a measure for vascular function, is reduced in type 1 diabetic rats [8] and type 1 diabetic patients [9] when compared to normoglycaemic controls. There are currently limited data available on myocardial perfusion in glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…68 Finally, myocardial blood flow reserve is abnormal in individuals with diabetes without epicardial coronary disease, 69 and there is reduced myocardial capillary density. 70 Hypertension and renal dysfunction in type 2 diabetes mellitus Diabetic nephropathy, a common consequence of T2DM, leads to accelerated cardiovascular disease and hypertension. Patients with diabetes, hypertension and LV hypertrophy have a high incident rate of heart failure (1.9%).…”
mentioning
confidence: 99%
“…It affirms the concept that asymptomatic vasculopathy is present in individuals with prediabetes who are thus at high risk of developing cardiovascular complications. 16 This suggests that determination of blood viscosity in clinical practice may be a useful supplementary tool in the assessment of vasculopathy and SCVD in prediabetes and undiagnosed diabetes. The absence of difference between the DM and DM+CVD groups in the present study shows that oxidative stress risk in DM is as high as that in DM+CVD individuals, which has significant prognostic implications.…”
Section: Discussionmentioning
confidence: 98%